Effects of Kersen leaves extract (Muntingia calabura L.) on SGOT and SGPT levels of soft drink induced mice - Siddiq, Muhammad Nuzul Azhim Ash; Marliyati, Sri Anna; Riyadi, Hadi; Winarsih, Wiwin (Jurnal Gizi dan Pangan, 2019)
This study aimed to analyse the antioxidant activity, total phenols, and flavonoids of kersen leaves (Muntingia calabura L.) extract (KLE) and determine the hepatoprotective activity of KLE in soft drink induced mice. Soft drinks induction causes liver injuries which increases the serum glutamic oxaloacetic transaminase (SGOT) and serum glutamic pyruvic transaminase (SGPT) levels. Mice were divided into five treatment groups (n=5) and were given Tween 80 (1%) (normal control), Tween 80 (1%) and 7 ml soft drinks (negative control), KLE (1000, 1500, and 2000 mg/kg), and 7 ml soft drinks per oral once daily for 4 weeks. Antioxidant activity was measured by 2.2-diphenyl-1-picrylhydrazyl (DPPH) method. Total phenols and flavonoids were analyzed by Folin-ciocalteu colorimetric and aluminium chloride (AlCl3) method. The blood samples were collected for biochemical analysis. The result showed that the KLE antioxidant activity were 11.11+0.50 ppm. Total phenols and flavonoids detected in the KLE samples were 2.19+0.12 mgGAE/g and 2.43+0.24 mgQE/g respectively. Mice treated with KLE had a significantly lower (p<0.05) serum SGOT and SGPT levels than negative control group. In conclusion, KLE has a potential hepatoprotective activity that works in synergy with its antioxidant activity.